Screening of natural products atlas for identification of lead molecule to treat angina pectoris using bioinformatics approaches. : Identification of lead compound for Angina Pectoris Using CADD - Unnisa, Aziz; Jandrajupalli , Suresh B.; Elamine, Badria A; Mohamed, Omkalthoum A; Alreshidi, Khetam Saad; Alshammari , Aliyah Hamdan; Alshammari, Hajer shaty; Bandar, Norah; Gangireddy, Ramana (Cellular and Molecular Biology, 2023)
Angina pectoris is amongst the most common diseases. There is a scarcity of effective treatments for this disease. As a result, there is a significant clinical and social interest in predicting and developing novel compounds to treat cardiovascular disorders. So, specific natural products have been screened in this study because they have protective effects against angiotensin-converting enzymes. When taken orally, natural products can help protect against or lessen the severity of angina and heart damage. Natural compounds inhibit regulatory enzymes for controlling Angina. For this, we used computational methods such as drug design to identify novel natural compounds against cardiovascular diseases. Drug design via computational methods is gaining popularity as a quick and effective method to identify lead compounds in a shorter time at a low cost. This research work aims to predict novel lead inhibitor compounds against ACE to treat angina pectoris. This would ensure that, in early preclinical studies, there will be lower failure rates due to the demonstrated safety profiles of the predicted compounds.